Electromyoneurography and laboratory findings in a case of Guillain-Barré syndrome after second dose of Pfizer COVID-19 vaccine. Issue 11 (2nd November 2021) - Scendoni, Roberto; Petrelli, Cristina; Scaloni, Giorgia; Logullo, Francesco Ottavio
ABSTRACT: Guillain-Barre syndrome (GBS) is an acute immune-mediated disease of the peripheral nerves and nerve roots (polyradiculoneuropathy) that is usually elicited by various infections. We present a case of GBS after receiving the second dose of Pfizer-COVID 19 vaccine. Diagnosis was made after performing an accurate clinical examination, electromyoneurography and laboratory tests. In particular, anti-ganglioside antibodies have tested positive. During this pandemic with ongoing worldwide mass vaccination campaign, it is critically important for clinicians to rapidly recognize neurological complications or other side effects associated with COVID-19 vaccination.